URGENSI LEBEL HALAL UNTUK PRODUK UMKM - Siti Aisyah; Yeni Fatur Rohmah (IZZI: Jurnal Ekonomi Islam, 2022)
In Indonesia, the definition of MSMEs is regulated in the Law of the Republic of Indonesia No. 20 of 2008 concerning MSMEs. Article 1 of the law states that micro-enterprises are productive businesses owned by individuals or individual business entities that have the criteria for micro-enterprises as stipulated in the law. Halal label is the provision of a halal sign or written evidence as a guarantee of a halal product with Halal writing in Arabic letters, other letters and a motor code from the Minister issued on the basis of a halal inspection from a halal inspection agency established by MUI. The purpose of this journal is to provide an overview of the understanding of MSME actors about the urgency of the halal label on MSMEs. This type of research uses qualitative methods. the definition of methodology as a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of this study indicate that halal certification is a very important instrument in ensuring business continuity and efforts to strengthen MSMEs, as evidenced by its positive influence on buying interest and purchasing decisions on MSME products. Halal certification is also proven to have a positive influence in increasing sales or turnover of MSMEs.